Pelatihan Dasar Elektronika Menggunakan Arduino dan Simulasi TinkerCad Untuk Guru SMP Kristen Harapan Bagi Bangsa Cilincing - Mulyadi, Melisa; Indriati, Kumala; Wijayanti, Linda; Olivia Sereati, Catherine; Octaviani, Sandra (Jurnal Pengabdian Masyarakat Charitas, 2024)
Community service activities organized by the Faculty of Engineering at Unika Atma Jaya with the theme of providing basic electronics skills to junior high schools (SMP) at SMP Kristen Harapan untuk Bangsa Cilincing, North Jakarta have been held 2 (two) times. This program received a positive response from teachers and students in grade 1 of junior high school. In previous activities, teachers had not been involved in the process, so that program continuity could not be implemented routinely in schools. Therefore, in this PKM activity, basic electronics training will be focused on teachers. The aim of this training is to provide training for teachers so that in the future SMP Kristen Harapan untuk Bangsa can organize extracurricular programs regarding the basics of electronics. In this training, teachers receive training using the TinkerCad simulation program, which is a simulation program for assembling electronic circuits. The teachers also had the opportunity to assemble a series of simulation results of running lights and microcontrollers on the project board. Based on the feedback, teachers from different educational backgrounds were able to assemble and run a series of simulation results. It is hoped that in the future teachers can provide this training to their students.